COMPARATIVE STUDY OF METHODS FOR THE DETERMINATION OF ANTIBIOTICS IN MILK AND DAIRY PRODUCTS - Sakieva Z.Zh; Muratbekova K.M; Boranbaeva T.K; Akhlan T.B; Ametova M.M (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this work, a comparative study of methods for determining antibiotics in milk and dairy products, ensuring the uniformity of measurements and characteristics, and measurement errors was carried out.